1997
DOI: 10.1093/hmg/6.11.1891
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Melanocyte Stimulating Hormone Receptor Variant Alleles in Twins with Red Hair

Abstract: The association between MSHR coding region variation and hair colour in humans has been examined by genotyping 25 red haired and 62 non-red Caucasians, all of whom were 12 years of age and members of a twin pair study. Twelve amino acid substitutions were seen at 11 different sites, nine of these being newly described MSHR variants. The previously reported Val92Met allele shows no association with hair colour, but the three alleles Arg151Cys, Arg160Trp and Asp294His were associated with red hair and one Val60L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
320
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(341 citation statements)
references
References 26 publications
17
320
2
2
Order By: Relevance
“…A number of polymorphic studies of the MC receptor are related to incidence of melanoma (Box et al, 1997;Jiménez-Cervantes et al, 2001). However, not all studies are in agreement (Ichii-Jones et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of polymorphic studies of the MC receptor are related to incidence of melanoma (Box et al, 1997;Jiménez-Cervantes et al, 2001). However, not all studies are in agreement (Ichii-Jones et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function polymorphic variants exist (Valverde et al, 1995) and are associated with red-haired individuals who pigment poorly (Schiöth et al, 1999). Reports also suggest that MC-1R polymorphisms correlate with cutaneous melanoma (Box et al, 1997;Jiménez-Cervantes et al, 2001), although not all studies have confirmed this (Ichii-Jones et al, 1998).…”
mentioning
confidence: 99%
“…In mammals the orthologue of the MC1R gene, the extension locus (e), was found mutated in those with red and yellow coat colours (Robbins et al, 1993;Vage et al, 1997). Studies on the molecular basis of the red hair and pale skin phenotype in humans have shown that the MC1R gene plays a role in this pigmentation type (Valverde et al, 1995;Box et al, 1997;Koppula et al, 1997;Smith et al, 1998;Rana et al, 1999). Various MC1R mutations have been identified in individuals with this and other pigment phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In humans MC1R variants have been associated with sunsensitive skin types I and II (Valverde et al, 1995;Koppula et al, 1997), suggesting a predisposition to cancer in individuals with MC1R mutations. Specific variants that have been found to be associated with the red hair and pale skin phenotype; R151C, R160W and D294H (Box et al, 1997;Smith et al, 1998) were found to be significantly associated with cutaneous malignant melanoma (CMM) (Palmer et al, 2000). It has been suggested that the presence of these variants alters the pigmentation phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth drawing attention to apparent discrepancies in the literature. First, studies relating phenotype to genotype need to take account of which alleles are thought to be important (1,38,39,(45)(46)(47)(48)(49)(50). If only some alleles are studied, then genuine associations may be missed; this indeed seems to be the case.…”
Section: The Diversity Of Mc1r Allelesmentioning
confidence: 99%